An MPC algorithm for offset-free tracking of constant reference signals - Betti, G.; Farina, M.; Scattolini, R. (2012 IEEE 51st IEEE Conference on Decision and Control (CDC), 2012)
A model predictive control (MPC) technique for tracking piecewise constant reference signals is presented. The controlled system is assumed to be linear, time invariant and subject to constraints on both inputs and states. In order to reject constant disturbances and to guarantee offset-free regulation also in presence of model/plant mismatch, the control loop is enlarged with integrators, and the system is described in "velocity form". The tracked reference signal is regarded to as one of the optimization variables, so that feasibility is guaranteed also for unfeasible desired references. Stability results are given, and a simulation example is reported.